Proposed Marketing Strategy for Terracotta (The Indonesian Journal of Business Administration, 2021)
Urban life which is synonymous with traffic jams, congestion, and busyness causes boredom. This boredom can have an impact on decreasing one's productivity at work. This phenomenon creates a new trend for nature tourism because it assesses that air quality is better and away from congestion. One of the most popular cities for traveling is Sukabumi. The tourism industry is one of the main contributors to Indonesia's GDP. With this phenomenon, the competition is getting tougher. Terracotta as one of the industry players in Sukabumi has not shown good results. Regarding Terracotta trying to improve its facilities through analysis of current business conditions. The researcher conducted an internal analysis using the 4P marketing mix analysis to determine the current conditions, the lack ofpromotion made Terracotta difficult to reach the market. This underutilization meant Terracotta was not well known, so his reputation had not yet been established. In addition, Terracotta does not yet have facilities and activities that support and can be carried out by customers while staying at Terracotta. Then the researchers conducted an external analysis using competitor analysis and customer analysis, Terracotta has problems in competition. Terracotta's competitors took precedence and were better known. They also have promotional media such as websites and billboards to attract customers to visit their villas. Competitors also have facilities and activities that support overnight stays. To get more customers, Terracotta needs to expand its facilities by building various facilities and activities. The construction of the villa is adjusted to the customer analysis that has been carried out previously to suit customer needs. To reach a wider market, Terracotta needs to carry out promotional activities. Promotional activities are carried out both online and offline.Keywords: Tourism Industry; Villas; Marketing Strategies.